Análise das concepções de estudantes de uma escola estadual adjacente a uma área de proteção ambiental sobre doenças causadas por vetores de arboviroses em Manaus, Amazonas - Silva, Andreza Carvalho da (Brasil, 2022)
Arboviruses are a public health problem because of the potential of the dispersal vector mosquito, its ability to adapt to new environments and hosts, and the possibility of causing epidemics. In Brazil, the main arboviruses are Dengue, Chikungunya and Zika, since arboviruses that cause these diseases obtain the same vectors that are commonly found in urban areas (Aedes aegypti and Aedes albopictus), due to the fact that the urban area offers conditions favorable to the development of these vectors, such as warmer climate, artificial and natural breeding sites for oviposition and population density. Despite these data, there are few studies in the Amazon regarding knowledge of urban populations in relation to the environment and interaction with the population. Thus, the school is a starting point for introducing health education so that students later disseminate information in society. From this perspective, the general objective of this work was to analyze the conceptions of the students of the third year of the High School of the State School Deputy Josué Claudio de Souza adjacent to the Environmental Protection Area (APA) of the Federal University of Amazonas (UFAM) about diseases caused by vectors. of arboviruses. Given the proximity of this population to one (APA). To analyze the students' conception of the subject matter, a structured questionnaire was applied and the data collected were analyzed in a qualitative and quantitative manner. Entomological collections were performed at the peridomicile, forest edge and forest, to survey arbovirus vector mosquitoes, to finally show the data to the students, these data were quantified, identified and tabulated. From the analysis of the questionnaires, it was possible to conclude that the students have a satisfactory basic level of knowledge about the main arboviruses in Brazil, since the students correctly answered the questions corresponding to most categories of the questionnaire. However, only 23.3% were able to associate the presence of mosquitoes in the school due to the anthropization process of APA-UFAM. This is alarming given that vectors of arboviruses (Aedes aegypti and Aedes albopictus) and species with records of natural arbovirus infections (Limatus durhamii) were found in the school. On the forest edge (Trichoposopon digitatum) and in the forest (Sabethes glaucodaemon and Trichoposopon digitatum) were found mosquitoes that are naturally infected with arboviruses that can be transmitted to humans. Based on the analysis of the questionnaires, a lecture was held to explain the existing doubts and the relationship between the natural environment and the urban environment, their consequences due to the anthropization process related to the public health problem, arboviruses.